Peningkatan Keterampilan Menulis Teks Biografi Bentuk Infografis Dengan Pembelajaran Project Based Learning Pada Kelas X7 Di SMA Negeri 1 Magetan - Ahmad Muzaqi; Vivi Rulviana; Rinto Sri Wuryaningsih (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
The purpose of this class action research is to improve the skills of writing biographical texts in the form of infographics with a project based learning model in class X7 at SMA Negeri 1 Magetan. The background of this research is the low skills of writing biographical texts in the form of infographics in the class X7 students. This research method uses a qualitative descriptive method. The classroom action research (CAR) process uses planning, action, and reflection steps. The data analysis used was a comparative descriptive technique and data collection used tests and observations. Based on the results of data analysis and observations made which consisted of 2 cycles and each cycle was divided into 2 face-to-face meetings as follows. In cycle I students get an average score of 71.74, that value (has not reached) Minimum Completeness Criteria (75) and continued in cycle II with an average score of 84.11 with a total of 28 students out of 35 students. The conclusion is that the learning outcomes of the learning model with the PJBL learning model in learning biographical texts can improve students' skills in writing logically and creatively. Keyword: Writing Skills; Biographical Texts; PJBL; Clasroom Action Research.